Export and isotropic composition of organic matter in the Subantarctic and polar frontal zones of the Southern Ocean - Lourey, Martin John (2003)
This thesis aims to improve estimates of net community production and carbon export in the Subantarctic (SAZ) and Polar Frontal Zones (PFZ) of the Southern Ocean from estimates of nutrient depletion, and to use measurements of stable isotopes in suspended and sinking organic matter to assess ecosystem processes responsible for nitrate and CO2 depletion. Estimates of seasonal surface water nutrient depletion corrected for frontal movements and changes in water masses using observed quasi-linear nutrient-salinity relationships, suggest that from July to March nitrate depletion and carbon export in the SAZ (510 mmol N 111 -2 and 3,400 mmol C m-2 ) was approximately twice that of the PFZ (250 mmol N m-2and 1,600 mmol C m -2 ). Phosphate depletions were similar (29 and 24 mmol P m -2for the SAZ and PFZ, respectively) between the regions due to a lower N/P ratio of depletion in the PFZ (8.3 ¬¨¬± 5.4) than the SAZ (15.1 ¬¨¬± 2.3). Comparison with sediment trap and primary production estimates suggests that differences in nitrate depletion are the result of differences in production. However, the relative magnitude of export in the two zones remains uncertain because resupply of nutrients from the south may lower the observed nutrient depletions in the PFZ. Only 2 to 3% of the material leaving the surface reaches deep water sediment traps deployed at 800 to 1000 m, suggesting most organic carbon is remineralised and its constituent nutrients and CO2 transported to lower latitudes in the Antarctic Intermediate and Subantarctic Mode Waters.